2021
DOI: 10.21203/rs.3.rs-156798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the Most Suitable Reference Gene for Gene Expression Studies With Development and Abiotic Stress Response in Bromus Sterilis

Abstract: Bromus sterilis is an annual weedy grass, causing high yield losses in winter cereals. Frequent use of herbicides had led to the evolution of herbicide-resistance in this species. Mechanisms underlying herbicide resistance in B. sterilis must be uncovered because this problem is becoming a global threat. qRT-PCR and the next-generation sequencing technologies can contribute to elucidation of the resistance mechanisms. Although qRT-PCR can calculate precise fold changes, its preciseness depends on the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Also, when performing NormFinder analysis (another tool for calculation of stability), HMBS exhibited the highest stability in tissue samples among the five candidate reference genes (data not shown). In conclusion, HMBS was selected as the most stable reference gene in tissue, serum and serum exosomes based on Bestkeeper, a software that identifies the suitable reference gene (39). Additionally, NormFinder analysis revealed that HMBS is the most stable reference gene for tissue samples.…”
Section: Resultsmentioning
confidence: 99%
“…Also, when performing NormFinder analysis (another tool for calculation of stability), HMBS exhibited the highest stability in tissue samples among the five candidate reference genes (data not shown). In conclusion, HMBS was selected as the most stable reference gene in tissue, serum and serum exosomes based on Bestkeeper, a software that identifies the suitable reference gene (39). Additionally, NormFinder analysis revealed that HMBS is the most stable reference gene for tissue samples.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time polymerase chain reaction (RT-qPCR) is easy to perform with high sensitivity and speci city, which provides the accuracy and produces reliable as well as rapid quanti cation results [25,26], therefore it has emerged as a robust and widely used methodology for gene expression. To date, some plants have been selected for research on RT-qPCR analysis, including Glycyrrhiza [27], Nitraria tangutorum [20], Fucus distichus [28], Bromus sterilis [19], Allium tuberosum [29], and Suaeda glauca [30]. In addition, RT-qPCR is widely used in diagnosing diseases, such as preterm birth [31], diabetic kidney disease [32], Bronchopulmonary dysplasia [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Gossypium hirsutum L. salt stress, UBQ7, GAPDH and EF1A8 were the better reference genes in leaves, while the better reference genes were TUA10, UBQ7, CYP1, GAPDH and EF1A8 in roots [18]. For Bromus sterilis, three developmental stages (2-leaves stage, 3-leaves stage and 4-leaves stage), 18S rRNA and ACCase were the better reference gene [19]. Under ABA treatment, the ideal reference genes of Nitraria tangutorum were EF1-α and His [20].…”
Section: Introductionmentioning
confidence: 98%